An Improved User Authentication Protocol for Healthcare Services via Wireless Medical Sensor Networks. (26th April 2014) - Khan, Muhammad Khurram; Kumari, Saru
Abstract : Healthcare service sector is one of the major applications of Wireless Sensor Networks (WSNs) acknowledged as Wireless Medical Sensor Network (WMSNs). It deploys tiny medical sensor-nodes ( MS -nodes) on the body of the patient to sense crucial physiological signs which can be accessed and analyzed by registered medical professionals. Recently, Khan et al. analyzed Kumar et al.'s scheme proposed for healthcare applications using WMSNs and observed that the scheme is susceptible to many security weaknesses if an adversary extracts the information from the lost smart card of some user. The adversary can access patient's physiological data without knowing actual password, can deceive medical professionals by sending fake information about patients, can guess the password of a user from the corresponding smart card, and so forth. Besides, the scheme fails to resist insider attack, lacks user anonymity and the session key shared between the user and the MS -node is insecure. To overcome these problems, we propose an improved user authentication scheme for healthcare applications using WMSNs. We show that the scheme is free from the identified weaknesses and excels in performance and efficiency scheme.